Establishing a Crown Agency Amid Multiple Service Providers - Lisette Dansereau; Mary Jean Hande; Christine Kelly (McMaster University Library Press, 2019)
Directly funded (DF) home care is a policy mechanism where individuals are given funds to arrange their own services by hiring people in their communities or by subcontracting to service provider organizations. In 2017, the Ontario Ministry of Health and Long-Term Care briefly established a crown agency called Self-Directed Personal Support Services Ontario (SDPSSO). The stated goal of the SDPSSO was to create a DF home care program to serve older people, expanding an existing Ontario program serving a small number of younger adults with disabilities. The development of SDPSSO was influenced by the then health minister's ideological belief, pressure to reform home care from multiple stakeholders, and positive (although sparse) international evidence of the efficacy of DF home care among older adults. Reaction to the policy shift included a judicial injunction brought forward by a coalition group of home care service providers, halting implementation. A SWOT analysis shows that the SDPSSO provided as many threats and unknowns as there were possible benefits. A change in provincial government resulted in the dissolution of the SDPSSO in 2018 and the introduction of a family-managed program that continues to exclude older people. It is unclear what future changes may be in store for home care in Ontario. Le programme de financement direct (FD) des soins à domicile consiste à transférer des fonds aux individus pour qu'ils mettent en oeuvre eux-mêmes les services dont ils ont besoin en recrutant au sein de leur communauté ou en sous-traitant à des organismes fournisseurs de services. En 2017, le Ministère de la Santé et des Soins de Long-Terme de l'Ontario a mis en place un éphémère organisme de la couronne appelé Services de Soutien à la Personne Autogérés de l'Ontario (SSPAO). L'objectif affiché de SSPAO était de créer un programme de FD pour les personnes âgées, par extension d'un programme déjà en place pour une population restreinte de jeunes adultes handicapés. Le développement de cet organisme peut s'expliquer par une préférence idéologique du ministre de l'époque, des pressions de multiples origines pour réformer le système des soins de long-terme à domicile et des éléments de preuve rares mais favorables sur l'efficacité des soins à domicile FD pour les personnes âgées. En réaction à ce changement de politique, une coalition de producteurs de services de soins à domicile a déposé une injonction en justice, freinant la mise en place de l'organisme. Une analyse FFOM (SWOT) montre que le SSPAO engendrait autant de menaces et d'inconnues que d'avantages possibles. Un changement de gouvernement provincial a conduit à la dissolution du SSPAO en 2018 et à l'introduction d'un programme de gestion familiale qui continue à exclure les personnes âgées. L'avenir des soins à domicile en Ontario est pour le moins incertain.